PENDIDIKAN NABI YA’QUB TERHADAP NABI YUSUF (STUDY SURAH YUSUF) PERSPEKTIF TAFSIR AL MISBAH - Tiyo Mustakim; Ainur Rha’in (JURNAL ILMIAH EDUNOMIKA, 2024)
This article examines the education of the prophet Ya'qub towards Yusuf in the view of the interpretation of al-Misbah. This research takes the form of library research with a qualitative approach. The data collection used is documentation. This writing uses the tafsir of Al-Misbah as a reference. Data analysis using content analysis method. And found that the success of the Prophet Yusuf was a form of his parents' upbringing, with all the attitudes that the Prophet Ya'qub showed towards him, including: with compassion, patience, forgiveness, remaining confident and not giving up on the grace of Allah SWT.